Biopriming with Trichoderma harzianum: an effective tool for management of soil borne diseases of safflower: Biopriming with Trichoderma harzianum: an effective tool for management of soil borne diseases of safflower - C V AMBADKAR; S B GHUGE; S V PAWAR; S A SHINDE (Journal of Oilseeds Research, 2023)
An effect of biopriming with Trichoderma harzianum on different soil borne diseases of safflower was studied at three consecutive year 2018-19, 2019-20 and 2020-21 using safflower variety safflower variety PBNS-12. Safflower seed biopriming with Trichoderma harzianum @ 10g/litre water for 12 hrs (10 gm Thz + 1 ltr water + 1 kg seed + 12 hrs soaking) before sowing was found very effective and economical management of Phytophthora seedling blight, Fusarium wilt and Rhizoctonia root rot diseases of Safflower.